RETRACTED: Solutions to minimise waste formation at machine-building enterprises - Galkina Elena; Terehov Aleksandr; Nikitin Egor; Zhelnina Daria; Zachinyaeva Alexandra (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001